Bolted in the nasopharynx: case report of an unusual foreign body in a child - Sagar, Poonam; Bhardwaj, Viny; Lepcha, Sangay Choden; E. J., Arun (International Journal of Contemporary Pediatrics, 2024)
Foreign bodies of the aerodigestive tract can land otolaryngologists in a tough spot. The complexity of the situation increases even more in paediatric patients where a satisfactory examination is often difficult to achieve. Of all the location in upper airway, nasopharynx is deemed as an uncommon spot for lodgement of foreign bodies, especially when ingestion is the route of entry of foreign substance. The role of imaging and nasopharyngoscopy is often undermined. We present the case of a 2-year-old child who presented with an alleged history of ingestion of a foreign body. Clinical examination showed mucoid discharge in bilateral nasal cavities. The examination performed was limited since the child was irritable. Based on the suspicious history given by the child’s guardian, a plain radiograph was ordered. On radiological evaluation, a radio-opaque object was seen lying at the nasopharynx. A controlled setting with secured airway was chosen as the plan and the child was taken up in emergency for foreign body removal under general anaesthesia. The retrieved object was a metallic nutbolt which presumably got lodged in the nasopharynx by digital manipulation done by the guardian or during a bout of vomiting. Ingested foreign bodies being found in the nasopharyngeal is a rare occurrence altogether. However, whenever feasible, a nasopharyngoscopy should be given due consideration. Radiology is an excellent supplemental tool in cases where a thorough examination is not possible.